Copper chelation therapy in intrahepatic cholestasis of childhood. Issue 1 (January 1983) - Evans, J; Zerpa, H; Nuttall, L; Boss, M; Sherlock, S
Abstract : The effect of copper chelation was studied in a group of children with intrahepatic cholestasis of childhood (IHCC) and increased liver copper levels. Initial therapy was D-penicillamine (10 mg/kg/day), being replaced by triethylenetetramine dihydrochloride (20 mg/kg/day) when side-effects of D-penicillamine occurred. Eight children completed two years of copper chelation. Pruritus remained the main symptom and did not improve. Two patients developed D-penicillamine side-effects - one patient after nine months (marked anorexia, lassitude) and one other patient after 19 months (thrombocytopenia). Two patients died during the study, in one of these normal hepatic copper concentration was achieved. Hepatic copper concentrations decreased in seven of eight patients from 8.6 (2.7 +/- 16.2) mumol/g to 3.4 (0.6-16.5) mumol/g (median and range (0.05 less than 0.01) and serum aspartate transaminase increased in seven of eight patients (p less than 0.05). Histological assessment of serial liver sections revealed increased fibrosis and cholestasis despite reductions in hepatic copper levels during the study. This study showed that D-penicillamine therapy was associated with significant side-effects, while marked clinical, biochemical, or histological improvement did not follow effective copper chelation therapy in intrahepatic cholestasis of childhood.